Twentieth Century Fund Report on Improving Public Schools. (Education Digest, 1983)
This article focuses on a report of the research foundation Twentieth Century Fund about improving public schools in the U.S. Public schools in the U.S. are in trouble. Disaster can be averted only if there is a national commitment to excellence in the public schools. While the Twentieth Century Fund Task Force strongly favors maintaining the diversity in educational practices that results from decentralization of schools, schools must, at minimum, provide the same core components to all students: basic skills of reading, writing, and calculating, technical capability in computers, training in science and foreign languages, and knowledge of civics. The schools should also foster understanding, discipline, and discernment, and impart a desire to acquire a range of knowledge. The schools must make a concerted effort to improve their performance, and there is a clear national interest in helping schools everywhere to do so. That interest can be asserted and dramatized most effectively by the federal government, which is in the best position to focus public attention on the vital importance of quality in the schools and to support its attainment. The report calls on the executive and legislative branches of the federal government to emphasize the need for better schools and a better education for all young Americans.